Histologic characterization of experimental cutaneous leishmaniasis in mice infected with Leishmania braziliensis in the presence or absence of sand fly vector salivary gland lysate - Donnelly, K.B; Lima, H.C; Titus, R.G (The Journal of parasitology, 1998)
Leishmania braziliensis is the causative agent of human cutaneous leishmaniasis in parts of the New World. In the murine model of infection, L. braziliensis does not produce severe or lasting cutaneous lesions in either BALB/c or C3H mice. However, when the parasites are injected into BALB/c mice with salivary gland lysate of the sand fly vector for the parasite, infection is significantly enhanced, as measured by lesion size, parasite burden, and the outcome of infection. Histologic examination of these cutaneous lesions showed that initially, nodular and diffuse dermal infiltrates of neutrophils, eosinophils, and histiocytes occurred in all mice. Over time, the saliva-free lesions progressed to small organized granulomas of epithelioid macrophages that contained few parasites, with eventual resolution of inflammation and mild dermal fibrosis. The saliva-associated lesions progressed to extensive, poorly organized accumulations of heavily parasitized epithelioid macrophages, with persistent neutrophils and eosinophils, and minimal fibroplasia. These results indicate that sand fly salivary gland lysate markedly modifies the inflammatory response to infection with L. braziliensis.